Development of test instruments to measure problem-solving and science literacy of grade XI students on ion equilibrium material in salt hydrolysis - Santi Novita; Susilawati Susilawati; Radjawaly Usman Rery (Pascasarjana Universitas Negeri Medan, 2024)
Low science literacy in students will have an impact on students' ability to solve problems. To improve it, it is necessary to develop an assessment instrument in the form of a science literacy instrument. This study aims to develop valid, reliable problem solving and science literacy assessment instruments for students. The material chosen is ion equilibrium in salt solution. The research was conducted in high, medium and low ability schools namely SMA Negeri 1 Pekanbaru, SMA Negeri 12 Pekanbaru and SMA Negeri 15 Pekanbaru. There are 16 questions out of 20 questions that are constructively valid with a correlation value> 0.36. The questions developed have met the reliability requirements with a Cronbach alpha coefficient value greater than 0.6, reaching a value of 0.874. The level of difficulty of questions between 0.3 -0.7 is in the good enough category and differentiating power â‰¥ 0.3. Based on two trials, namely one-on-one trials and limited trials, the same results were obtained that the assessment instruments developed for students had very good readability aspects (85%), good adequacy aspects (64%) and assessment instruments developed for teachers had very good feasibility aspects (91%). There is a significant difference in the ability of students in high schools with medium and low ability schools.